The Effect of Duolingo Application on the Students’ Achievement in English Vocabulary at SMPN 1 Langke Rembong - Kurnianto, Yohanes Tresno; Guna, Stanislaus; Halum, Yustus Sentus (Universitas Sebelas Maret, 2023)
This research aimed to determine the significant effect of the Duolingo application in teaching English vocabulary, i.e., to find out whether students who are taught using the Duolingo application have better achievement compared to students who are not taught using the Duolingo application. This research used a quasi-experimental design and the test as the research instrument. This research was conducted on the second-year students of SMPN Langke Rembong in the 2022-2023 school year, with a total sample of 58 students and using purposive sampling to determine the sample. Based on the data analysis results, the experimental and control groups had different mean scores. While the experimental group obtained a mean score of 85.67, the control group had a mean score of 71.14. The mean score results concluded that the experimental group had a higher mean score than the mean score obtained by the control group. Furthermore, the hypothesis test results demonstrated that the null hypothesis (Ho), stating no significant difference in vocabulary scores or achievement between students who were taught by Duolingo applications and those who were not taught by Duolingo applications, was rejected. Meanwhile, the alternative hypothesis (Ha) was accepted. In other words, there is a significant difference in vocabulary scores or achievement between students who were taught by the Duolingo application and those who were not taught by the Duolingo application